Sustainable renewable energy system installations through qualified and skilled: TRAINEE approach - Stojanovska-Georgievska, L; Sandeva, I; Krleski, A; Spasevska, H; Ginovska, M (IOP Publishing, 2020)
Renewable energy and use of renewable energy sources (RES) is seen as part of the appropriate response to the global concerns for energy efficiency and greener world leading to a rapid increase in demand for renewable energy specialists who are able to design, install and maintain such systems. There are very few initiatives for more systematic approach for designing educational programs and developing curricula for training for designers and installers of RES systems in buildings. This especially refers to developing separate occupational standards, recognized by the national qualification frameworks, which will ensure formal validation of developed qualifications. The aim of this paper is to provide a model for training courses for designers and installers of small-scale renewable energy systems in buildings. This model is based on the experience of TRAINEE project, which had the aim to implement training courses for designers and installers of RES systems in buildings.
Keywords: skills, RES, installtions